Educational Attainment at Age 10–11 Years Predicts Health Risk Behaviors and Injury Risk During Adolescence - Demmler, Joanne C. (J Adolesc Health, 2017)
PURPOSE: To examine the effect of educational attainment in primary school on later adolescent health. METHODS: Education data attainments at age 7 and 11 were linked with (1) primary and secondary care injury consultation/admissions and (2) the Health Behaviour in School-aged Children survey. Cox regression was carried out to examine if attainment in primary school predicts time to injury in adolescence. RESULTS: Pupils that achieve attainment at age 7 but not at age 11 (i.e., declining attainment over time in primary school) are more likely to have an injury during adolescence. These children are also more likely to self-report drinking in adolescence. CONCLUSIONS: Interventions aimed at children with declining attainment in primary school could help to improve adolescent health.